turnover THE EFFECT OF PERCEPTION OF ORGANIZATION SUPPORT TO ORGANIZATIONAL COMMITMENT AND TURNOVER INTENTION EMPLOYEE HOTEL KAJANE MUA UBUD - ., Fahrizal; Utama, I Wayan Mudiartha (E-Jurnal Manajemen; Vol 6 No 10 (2017), 2017)
The purpose of this study was to determine the effect of the perception of organizational support to organizational commitment as well as to determine the effect of perceived organizational support and organizational commitment to turnover intention at the Hotel Kajane Mua Ubud. This research was conducted on the employees of Hotel Kajane Mua Ubud, with a total sample of 49 people. The analysis technique used is path analysis (path analysis). The results showed that the perception of organizational support significant negative effect on turnover intention. Second, the perception of organizational support positive and significant impact on organizational commitment. Third, organizational commitment and significant negative effect on turnover intention. The implications that may occur from this research that the hotel can create a positive labor relations between employers and employees and among employees. Second, the company leaders must make the situation in the company feel as comfortable as possible. Third, workload balancing with the working capacity of the individual, so that the perception of organizational support and commitment can be realized oganisasi and turnover intention can be minimized